Knowledge about the assessment of dysmorphic red blood cells in urinary sediment in clinical laboratory professionals in metropolitan Lima - Saldaña-Orejón, Italo Moisés (2022)
Background: Despite the existence of international guidelines for the correct assessment of dysmorphic hematuria, its categorization frequently presents a lot of variability, even among professionals in the same laboratory. Objective: To determine the level of knowledge of professional medical technologists for the assessment of dysmorphic red blood cells in urinary sediment. Material and Methods: Observational cross-sectional study. A measurement instrument was applied to assess knowledge about the preanalytical and analytical phase of the assessment of dysmorphic red blood cells in urinary sediment to 113 professionals with more than three years of experience in the area of ​​urinalysis and who work in state and private hospitals. Results. The mean score obtained was 5.4±1.9 out of 10 possible points; 85.0% of the respondents presented medium and insufficient knowledge and only 15.0% advanced knowledge; An association was observed between levels of knowledge and years of experience (p=0.006), no significant association was found with the variable gender (p=0.791) and hospital locations (p=0.888). Discussion: Low knowledge was evidenced in the preanalytical and analytical domains for the assessment of dysmorphic red blood cells, in addition to a significant association between the level of knowledge and the years of experience of the professional.